Spatial and temporal distribution of thyroid cancer incidence in China: An ecological study based on a national registry - Wen Liu; Jiaqi Yang; Zhenhao Zheng; Yang Yu; Jun Li; Ting Ma; Hao Liu (PLoS ONE, 2026)
The objective of this study was to analyze the incidence rate of thyroid cancer in China to elucidate its spatiotemporal distribution and to provide an evidence-based foundation for prevention and control strategies. Thyroid cancer incidence data from 2005 to 2018 were obtained from the China Cancer Registry Annual Reports (2008–2021). The Joinpoint regression model was used to describe the time trend, the age-period-cohort model was employed to analyze the effects of age, period and cohort on the thyroid cancer incidence, and spatial autocorrelation was used to analyze its spatial distribution. Results showed China's age-standardized incidence rate (ASIR) of thyroid cancer from 2005 to 2018 was 8.69 (95% CI: 8.55, 8.83) per 100,000, exhibiting an upward trend with an average annual percent change (AAPC) of 10.7% (95% CI: 9.5%, 11.9%). The ASIR was higher in urban than in rural areas, though its growth rate was lower than in rural areas; similarly, it was higher in females than males but grew slower than in males. Nationally, incidence risk initially increased and then declined with advancing age, while period effects showed an upward trend and cohort effects a downward trend. Spatial autocorrelation revealed clustered incidence patterns, with northeastern China exhibiting a high-high clustering. Although this study is limited by the lack of pathological classification, the delay in the latest data, and potential biases from the increasing number of surveillance sites, these findings also suggest that the national thyroid cancer surveillance system should be further strengthened, a registration system for high-risk populations should be established, and greater investment should be allocated to etiological research, such as through measures like controlling weight and regulating radiation to reduce the risk of thyroid cancer.